Principal's Strategic Management in School Revitalization: A Case Study on Learning Quality Improvement at SDN Inti Tomoli - Wiwin Wiwin; Rizal Rizal; Sisriawan Lapasere; Mahfud Mahmud Gamar; Muhammad Nazimuddin Al Kamil; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Despite growing interest in principal leadership, empirical studies examining how strategic management practices at the elementary school level translate into concrete learning quality improvements remain limited, particularly in underserved local contexts. This study aimed to analyze the principal's strategic management practices in school revitalization efforts and their implications for improving learning quality at SDN Inti Tomoli, Parigi Moutong Regency, Central Sulawesi, Indonesia. A qualitative descriptive approach with a case study design was employed. Data were collected through in-depth semi-structured interviews, structured observations, and student questionnaires involving the principal, teachers, school committee members, and 28 students from Grades IV–VI. Data analysis followed the Miles and Huberman interactive model. Five interconnected strategic management dimensions were identified: participatory learning planning aligned with the Independent Curriculum, teacher competency development, facilities revitalization with transparent budget governance, empowerment-based resource organization, and multi-stakeholder evaluation. These practices produced measurable improvements in instructional quality, student motivation, and school culture. A notable finding was that participatory organizational structures did not fully resolve disparities in teacher technology access. The findings confirm that principal strategic management is central to successful elementary school revitalization and sustainable learning quality improvement, while extending the literature by foregrounding budget transparency and culturally responsive pedagogy as consequential dimensions of effective revitalization management.